Unintended Consequences of Sensor, Signal, and Imaging Informatics: New Problems and New Solutions - Hughes, C.; Voros, S.; Moreau-Gaudry, A. (Yearbook of Medical Informatics, 2016)
Objectives: This synopsis presents a selection for the IMIA (International Medical Informatics Association) Yearbook 2016 of excellent research in the broad field of Sensor, Signal and Imaging Informatics published in the year 2015, with a focus on Unintended consequences: new problems and new solutions.Methods: We performed a systematic initial selection and a double blind peer review process to find the best papers in this domain published in 2015, from the PubMed and Web of Science databases. The set of MesH keywords used was provided by experts.Results: The constant advances in medical technology allow ever more relevant diagnostic and therapeutic approaches to be designed. Nevertheless, there is a need to acquire expert knowledge of these innovations in order to identify precociously new associated problems for which new solutions need to be designed and developed.
Keywords: Innovative technology; unintended consequences; novel solutions